Udział sił zbrojnych w procesie odsuwania od władzy biskupów aleksandryjskich podczas kontrowersji ariańskiej na wschodzie - Leszka, Małgorzata B. (Vox Patrum, 1999)
Within the short period of time between the years 339 and 373, Alexandria witnessed to a frequent use of the armed forces with an eye to removing the current bishop or enthronement of another, who had been approved of by the imperial court. Local administration officials and army officers were made use of in order to execute the current ruler’s orders.